Burnout among intensive care physicians and nurses in the post-pandemic era in China: a national cross-sectional study - Xin Li; Yue Zhang; Tian Li; Lina Zhao; Haiying Liu; Keliang Xie; Dongxue Huang; Yuehao Shen (BMJ Open)
Objectives In the post-pandemic era, few studies have examined burnout among professionals in intensive care units (ICUs) in China. This study aimed to investigate the prevalence of burnout and associated mental health problems, including depression and stress, among ICU physicians and nurses following the pandemic, and to explore the factors contributing to burnout.Design A cross-sectional design was used in this study.Setting This study was conducted in ICUs across hospitals in three distinct regions of China in 2023.Participants This study included 1488 ICU physicians and nurses, recruited through convenience sampling.Primary and secondary outcome measures Primary outcomes of this study were to investigate the prevalence of burnout and its associated factors among ICU physicians and nurses, as measured by the Maslach Burnout Inventory-Human Services Survey. As secondary outcomes, we aimed to explore mental health issues, including depression, assessed using the Patient Health Questionnaire, and stress levels, measured by Cohen’s Perceived Stress Scale.Results A total of 1447 participants were included in the study. Among them, 676 (46.7%) were physicians and 771 (53.3%) were nurses. 333 (49.3%) physicians and 458 (59.4%) nurses were found to have overall high burnout. 162 (24.0%) physicians and 247 (32.0%) nurses reported experiencing major depression, while 603 (89.2%) physicians and 601 (78.0%) nurses reported high levels of perceived stress. ICU physicians who were married (OR=0.607, 95% CI=0.392 to 0.940) had a lower risk of burnout, while those maintaining a neutral attitude to work-life balance (OR=1.621, 95% CI=1.022 to 2.571) might experience high burnout. Female ICU nurses (OR=0.698, 95% CI=0.500 to 0.974) who actively participated in epidemic prevention (OR=0.547, 95% CI=0.344 to 0.868) exhibited a reduced likelihood of suffering burnout. Higher burnout risks in ICU nurses were associated with working in teaching hospitals (OR=1.672, 95% CI=1.113 to 2.510) and a longer length of ICU stay for patients (OR=1.789, 95% CI=1.173 to 2.730).Conclusions ICU physicians and nurses in China are encountering significant burnout and mental health challenges following the pandemic. Possible risk factors for burnout encompass various dimensions, including individual, occupational and organisational levels. There is an urgent need to implement effective interventions to mitigate burnout, promote mental health and enhance the overall well-being of these healthcare professionals.